Analisis Bibliometrik: Peran Stakeholder dalam Eliminasi Tuberkulosis (TBC) - Putri, Natasya Aurora; Permana, Iip (Jurnal Kesehatan Komunitas, 2025)
This study was motivated by the limited number of systematic studies mapping the role of stakeholders in tuberculosis (TB) elimination efforts, despite the critical importance of this issue in achieving global health targets and the Sustainable Development Goals. The objective of this study is to analyze the landscape of scientific publications related to the role of stakeholders in TB elimination during the period 2014–2024. The focus of the study includes publication trends, main themes, topic focus intensity, and conceptual evolution. The method used is bibliometric analysis based on secondary data from 415 journal articles obtained through the Publish or Perish tool and selected using Mendeley. Furthermore, visual analysis was conducted using VOSviewer software to generate keyword co-occurrence maps, density maps, and temporal maps (overlays). The results indicate that scientific discourse is still dominated by medical themes and the implementation of public health programs. However, in recent years, there has been an increase in attention to the concept of broader stakeholder engagement, including corporate social responsibility (CSR) and the adoption of innovative technologies such as artificial intelligence. These findings support the urgency of a multisectoral approach to TB elimination, as emphasized in stakeholder theory. The conclusions of this study highlight a shift in research direction toward recognition of the contributions of non-traditional actors and technological innovation. Implications for practice